Upaya Peningkatan Sikap Net-Preneur Dan Prestasi Belajar Siswa Pada Mata Diklat E-Commerce Dengan Menggunakan Model Pembelajaran Project Work - ., Darsono (APMMI - Asosiasi Profesi Multimedia Indonesia, 2010)
ABSTRACT: The Increasing Efforts Attitude For Net-Prenuer and Student Achievements at E-Commerce Subject Matter Using Project Work Model in SMK 6 Surakarta in 2010/2011. One of the steps to face the job competition is to provide supplies to the students entrepreneurial skills. Equipping entrepreneurs to make them ready to work, ready to be independent, so that socio-economic problems can be reduced. One way to give the corresponding provision of the demand now is to teach entrepreneurship to use E-Commerce web. It means that students can be introduced to something new knowledge selling, trading via the internet based on Curriculum OF KTSP 2009, as contained in the Multimedia Department prepares students to be The Web Operator, then the competence of these students work ranging from making proposals, survey the field, taking pictures of products, negotiate with entrepreneurs, web design build, and upload to web hosting web. The Research Methods used descriptive and quantitative method through the portfolios of students' work. Subjects were students SMKN 6 Surakarta Multimedia class XI. The technique of data collection using the questionnaire (before and after quizes) as pretest and post test questions and student portfolios. The results showed the attitude of Net-Prenuer on students increases through the stages of treatment in cycle 1 for 3 class meeting : an active reflection of 17 students (47.2%), 69.4% and 72.2%. Through class meeting for three times in the cycle 2: shows the rate of activity is very active: 33.3% and is very active in the group reached 44.4%. The conclusion was that learning achievement areas of E-Commerce significant increase of 72% by value respectively 84.6 and 76.6 as many as 14 students by 22 students. Net-Preneurship understanding of student attitudes also increased simultaneously. Key Words : Net-Prenuer, E-Commerce Abstrak : Salah satu langkah untuk menghadapi persaingan kerja adalah dengan memberikan bekal kemampuan berwirausaha kepada anak didik. Pembekalan berwirausahan (Entrepreneurship) dapat menjadikan mereka siap bekerja, siap mandiri, sehingga permasalahan social ekonomi dapat direduksi. Salah satu memberikan bekal yang sesuai tuntutan sekarang adalah mengajarkan berwirausaha dengan menggunakan web E-Commerce. Artinya siswa mampu dikenalkan pada sesuatu pengetahuan baru berjualan, bertransaksi melalui internet, sebagaimana terdapat pada KTSP 2009 bahwa program Multimedia salah satunya menyiapkan siswa menjadi Operator Web , maka dengan kompetensi ini siswa bekerja mulai dari membuat proposal, survey lapang, mengambil gambar produk, bernegosiasi dengan pengusaha, merancang bangun web, serta mengupload web ke web hosting. Metode meneliti menggunakan deskriptif dan kuantitatif melalui protofolio hasil karya siswa. Subyek penelitian siswa SMKN 6 Surakarta kelas XI Multimedia, teknik pengambilan data menggunakan kuisioner awal, soal pretest dan post test serta portofolio siswa.Hasil penelitian menunjukkan sikap Net-Prenuer pada diri siswa meningkat melalui tahapan perlakuan pada siklus 1 selama 3 kali tatap muka : refleksi aktif 17 siwa (47,2%) , 69,4% dan 72,2%. Melalui tatap muka selama tiga kali pada siklus 2 : menunjukkan angka keaktifan sangat aktif : 33,3% dan sangat aktif mencapai 44,4% secara kelompok. Kesimpulannya adalah prestasi belajar bidang E-Commerce naik signifikan 72% dengan nilai masing-masing 84,6 sebanyak 14 siswa dan 76,6 sebanyak 22 siswa. Pemahaman sikap Net-Preneurship siswa juga meningkat secara simultan. Kata Kunci: E-Commerce, Net-Prenuer